Narrative identity: the construction of dignified masculinities in Black male sex workers' narratives. (2nd September 2019) - Peters, Simone M.; Kessi, Shose; Boonzaier, Floretta
ABSTRACT: This paper explores Black men's narratives of sex work in Cape Town. Sex work in South Africa takes place in a complex context of poverty and unemployment, which plays a part in men's entry into the profession. Much research on sex work has focused on female sex workers to the detriment of men who sell sex whose experiences are silenced. Narrative interviews were employed and the study investigated how Black men who sell sex position themselves and others and construct their identity within a workspace dominated by women. This paper is concerned with how men narrate about themselves, the language they employ to do so and its purpose. It is focused on the narratives that are told about the self and how these are co-constructed. It is additionally concerned with how men's talk constructs their experiences as intersectional. The analysis provides insight into how masculine identities are constructed in men's narratives about sex work.